A million drops - Árbol, Víctor del (Other Press, 2017)
"Gonzalo Gil is a lawyer stuck in a disaffected life, in a failed career, trying to dodge the constant manipulation of his powerful father. This monotonous existence is shaken up when he learns, after years without news of his estranged sister, Laura, that she has committed suicide in dramatic circumstances. Her death pushes the fragile balance of Gonzalo's life as both a father and husband to the limit"--